Clinical outcomes in patients with chronic lymphocytic leukemia with disease progression on ibrutinib - Paul J. Hampel; Kari G. Rabe; Timothy G. Call; Wei Ding; Jose F. Leis; Asher A. Chanan-Khan; Saad S. Kenderian; Eli Muchtar; Yucai Wang; Sikander Ailawadhi; Amber B. Koehler; Ricardo Parrondo; et al. (Blood Cancer Journal, 2022)
Abstract Patients with chronic lymphocytic leukemia (CLL) with disease progression on ibrutinib have worse outcomes compared to patients stopping ibrutinib due to toxicity. A better understanding of expected outcomes in these patients is necessary to establish a benchmark for evaluating novel agents currently available and in development. We evaluated outcomes of 144 patients with CLL treated at Mayo Clinic with 2018 iwCLL disease progression on ibrutinib. The median overall survival (OS) for the entire cohort was 25.5 months; it was 29.8 months and 8.3 months among patients with CLL progression (n = 104) and Richter transformation (n = 38), respectively. Longer OS was observed among patients with CLL progression who had received ibrutinib in the frontline compared to relapsed/refractory setting (not reached versus 28.5 months; p = 0.04), but was similar amongst patients treated with 1, 2, or ≥3 prior lines (18.5, 30.9, and 26.0 months, respectively, p = 0.24). Among patients with CLL disease progression on ibrutinib, OS was significantly longer when next-line treatment was chimeric antigen receptor T-cell therapy (median not reached) or venetoclax-based treatment (median 29.8 months) compared to other approved treatments, such as chemoimmunotherapy, phosphoinositide 3’-kinase inhibitors, and anti-CD20 monoclonal antibodies (9.1 months; p = 0.03). These findings suggest an unmet need for this growing patient population.